2017
DOI: 10.2298/pac1704265m
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the electrical and gas sensing properties of thick films prepared with synthesized nano-sized and commercial micro-sized Fe2O3 powders

Abstract: In this work, Fe2O3 nanoparticles (NPs) were successfully synthesized by Pechini sol-gel method. Scanning electron microscopy, transmission electron microscopy and X-ray diffraction characterizations were used to study the morphology and crystal structure of the synthesized products. The electrical and gas sensing behaviour of the synthesized and commercial Fe2O3 samples, prepared in the form of thick films, were studied. Though the commercial Fe2O3 powders had lower resistance but it was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…When the target gas (LPG, which is a reducing gas) was introduced into the chamber, it reacted with the chemisorbed oxygen on the sensor surface to produce water and carbon dioxide (Figure 7b). The surface reduction in the sensor's sensing layer led to the release of the captured electrons, causing the thinning of the depletion layer and resulting in increased conductivity of the sensor [39][40][41]. When helium was used as the carrier gas (Figure 7c), the sensor resistance (27.95 kΩ) was observed to be far lower than that observed when air was used (see Table 3).…”
Section: Gas Sensing Mechanismmentioning
confidence: 98%
See 1 more Smart Citation
“…When the target gas (LPG, which is a reducing gas) was introduced into the chamber, it reacted with the chemisorbed oxygen on the sensor surface to produce water and carbon dioxide (Figure 7b). The surface reduction in the sensor's sensing layer led to the release of the captured electrons, causing the thinning of the depletion layer and resulting in increased conductivity of the sensor [39][40][41]. When helium was used as the carrier gas (Figure 7c), the sensor resistance (27.95 kΩ) was observed to be far lower than that observed when air was used (see Table 3).…”
Section: Gas Sensing Mechanismmentioning
confidence: 98%
“…At an operating temperature of 225 • C, atmospheric oxygen is chemisorbed on the surface of the sensor as Ooxygen species (Figure 7a), as illustrated in Equations ( 2)-( 5). These oxygen species capture the free electrons at the conduction band, creating a depletion layer on the sensor [39,40], and thus increase the resistivity of the n-type sensor. When the target gas (LPG, which is a reducing gas) was introduced into the chamber, it reacted with the chemisorbed oxygen on the sensor surface to produce water and carbon dioxide (Figure 7b).…”
Section: Gas Sensing Mechanismmentioning
confidence: 99%
“…Many examples of ethanol sensors have been developed and show a remarkable sensing capacity [6][7][8]. In particular, we have shown that α-Fe 2 O 3 is an ideal candidate as a sensing material to be used in breath ethanol conductometric sensors [9,10].…”
Section: Introductionmentioning
confidence: 97%